A multiscale climate emulator for long‐term morphodynamics (MUSCLE‐morpho). Issue 1 (22nd January 2016) - Antolínez, José Antonio A.; Méndez, Fernando J.; Camus, Paula; Vitousek, Sean; González, E. Mauricio; Ruggiero, Peter; Barnard, Patrick
Abstract: Interest in understanding long‐term coastal morphodynamics has recently increased as climate change impacts become perceptible and accelerated. Multiscale, behavior‐oriented and process‐based models, or hybrids of the two, are typically applied with deterministic approaches which require considerable computational effort. In order to reduce the computational cost of modeling large spatial and temporal scales, input reduction and morphological acceleration techniques have been developed. Here we introduce a general framework for reducing dimensionality of wave‐driver inputs to morphodynamic models. The proposed framework seeks to account for dependencies with global atmospheric circulation fields and deals simultaneously with seasonality, interannual variability, long‐term trends, and autocorrelation of wave height, wave period, and wave direction. The model is also able to reproduce future wave climate time series accounting for possible changes in the global climate system. An application of long‐term shoreline evolution is presented by comparing the performance of the real and the simulated wave climate using a one‐line model. Key Points: Multivariate wave climate time series preserving seasonality, interannual variability and chronology Future wave climate time series accounting for possible changes in the global climate system Long‐term (decades) morphodynamic simulations